Iron status of exclusively breastfed low-birth-weight infants born to anemic mothers and effect of maternal iron supplementation for 3 versus 6 months: A randomized double-blind placebo control trial - Fatima, Tarannum; Faridi, Mohammad Moonis Akbar; Srivastava, Geetika (Frontiers in Pediatrics, 2022)
Background The effect of maternal iron supplementation during lactation on the iron status of exclusively breastfed low-birth-weight (LBW) infants is not known. Objective (1) To find out the number of LBW exclusively breastfed infants having hemoglobin < 10.5 g/dL at 6 months when mothers received iron. (2) To find out the proportion of anemic infants when mothers received iron for 3 and 6 months. Design The Clinical Trials Registry, India (CTRI) registered trial (CTRI/2018/08/015516) double-blind randomized control trial participants: A total of 80 anemic mothers and exclusively breastfed LBW infants. Intervention A total of 80 anemic mothers and exclusively breastfed infants, birth weight 1,500–2,499 g, randomized into two groups of 40 each. Mothers received daily iron for 3 months and placebo for the next 3 months in group A and iron for 6 months in group B. Iron profile of mothers and infants measured at recruitment and 6 months. Results In total, 26.6% infants developed anemia till 6 months of age, and number of anemic infants were similar whether mothers received iron for 3 (n = 9) or 6 months (n = 11). Hemoglobin (12.89 + 0.46 vs. 12.44 + 0.48 g/dL; p < 0.001) and serum ferritin (27.45 + 7.60 vs. 18.94 + 5.36 ng/mL; p < 0.001) were significantly higher in infants at 6 months of age whose mothers received iron for 6 months in comparison to 3 months. Conclusion: totally, 26.6% exclusively breastfed infants developed anemia till 6 months of age when mothers took iron; number of anemic infants were not different if mothers received iron for 3 or 6 months. A significant increase was noted in serum ferritin with slightly higher hemoglobin of infants when mothers received iron for longer duration. Clinical trial registration [http://ctri.nic.in/Clinicaltrials/pubview.php], identifier [CTRI/2018/08/015516].